Effects of healthy ageing on activation pattern within the primary motor cortex during movement and motor imagery: an fMRI study. - Nikhil Sharma; Jean-Claude Baron (PLoS ONE)
The increase in older adults over the coming decades will be accompanied by a greater burden of chronic neurological diseases affecting the motor system. The motor system adapts to maintain motor performance with the primary motor cortex (BA4) emerging as a pivotal node within this neuroplastic process. Studies of ageing often consider BA4 a homogenous area but cytoarchitectonic studies have revealed two subdivisions, an anterior (BA4a) and posterior subdivision (BA4p). Here we focus upon the effects of ageing on the involvement of BA4a and BA4p during movement and motor imagery (MI). Thirty-one right-handed healthy volunteers were recruited and screened for their ability to perform imagery (5 subjects excluded). The sample was split into an older group (n = 13, mean age 56.4 SD 9.4) and a younger group (n = 13, mean age 27.4 SD 5.3). We used an fMRI block-design (auditory-paced [1 Hz] right hand finger-thumb opposition sequence [2,3,4,5, 2...]) with MI & rest and actual movement & rest. We explored the distribution-based clustering and weighted laterality index within BA4a and BA4p. The involvement of BA4p during MI (measured with distribution-based clustering) was significantly greater in the older group (p<0.05) than in the younger group. Hemispheric balance of BA4p decreased with age during MI (Spearman rho -0.371; p<0.05), whereas that of BA4a decreased with age during actual movement (Spearman rho = -0.458 p<0.01). Irrespective of age, we found BA4 is involved during motor imagery, strengthening the rationale for its potential use in older subjects. These findings suggest that the functions of the subdivisions of BA4 are differentially affected by ageing and have implications regarding how ageing affects the cognitive processes underlying motor functions.